THE STUDY OF PROFITABILITY OF DWELLING RECONSTRUCTION OF FIRST MASS SERIES (Academic journal Industrial Machine Building Civil Engineering, 2019)
The study of organizational and technological factors on dwelling reconstruction profitability of first mass series with thepurpose to define the effective organizational solutions of reconstruction is described. The study is carried out on the basis ofexample of dwelling reconstruction of typical series 1-4382.5-7. The informative and graphical models of reconstruction aremade. The factors having impact on reconstruction indexes are defined. The plan of numerical experiment considering simultaneous impact of the given factors on the profitability index of reconstruction is made. With the help of experimental andstatistical modeling mathematical models of dependency of profitability on the factors in the form of charts are made.The charts analysis defined the areas of effective solutions by simultaneous impact of factors. By the results of studies theconclusions about the conditions of such dwellings reconstruction operations are made.
Keywords: charts; the areas of effective solutions; models of reconstruction; experimental and statistical modeling; organizational and technological factors